Update on H5N1 Panzootic: Infected Mammal Species Increase by Almost 50% in Just Over a Year - Plaza, Pablo (2025)
The current panzootic caused by the highly pathogenic avian influenza virus A(H5N1) (hereafter, H5N1) is having devastating effects on animal and ecosystem health; the virus has spread globally, causing alarming mortalities in a wide range of domestic and wild animals [1]. By early 2024, at least 50 mammal species had been reported infected by H5N1, with massive mortalities in some cases; viral mutations suggest the virus is adapting to infect mammals [2]. This epidemiological situation puts humans at risk due to the potential emergence of a new viral variant capable of triggering a new pandemic. Here, we provide a global update on mammals infected by H5N1 up to July 2025 following the methodology previously used by Plaza et al. [2], which is based on a search of scientific literature and diverse global databases.